Maps of major soil parameters: A reference for monitoring soil fertility in Burundi - Samson Musonerimana; Niyonkuru Anicet; Privat Ndayihanzamaso; Elena Semenova; Marie Chantal Niyuhire; Marcien Sendegeya; Salvator Kaboneka; Soter Ndihokubwayo; Oscar Nduwimana; Micael Beun; Anaclet Nibasumba (Sustainable Environment, 2025)
Soil fertility is a key factor for ensuring both the quantity and quality of agricultural production. To evaluate the fertility level, 1,377 soil samples were collected and analyzed from six AgroEcological Zones (AEZs) across Burundi. These samples were collected during June—July 2021 using a 4 km grid mesh. The geographical coordinates of each sampling point were recorded. The analyzed parameters included pH (water), soil organic carbon (SOC), total nitrogen (N), available phosphorus (P), exchangeable potassium (K), calcium (Ca), and magnesium (Mg). Fertility maps were developed using the Inverse Distance Weighting (IDW) method with sampling density of 0.25 samples/km2.Comparison of means were performed using Tukey’s test. Results showed significant differences soil parameters across AEZs. More than 73% of soils in all AEZs were highly acidic, 99% had low phosphorus availability and 53% had low potassium levels. Among AEZs, Congo-Nile Crest had the highest percentage of SOC and N, Imbo plain and North depressions had higher content of Ca, Mg. The spatial distribution of these parameters was heterogeneous, with strong variations even between nearby points within the same AEZ. This heterogeneity limits the possibility of providing general fertilization recommendations per AEZ, necessitating adaptations at the farm or low subdivision level.